Upcycling of Eggshell Waste into Calcium Phosphates for Use in Sustainable Biomedical Engineering Applications - Nikolaos Pagonis; Dimitrios Flegkas; Aikaterini Itziou; Konstantinos Kountouras; Adam Stimoniaris; Petros Samaras; Vayos Karayannis (Eng)
Eggshells are an inorganic waste, and their accumulation rate is increasing globally, complicating waste management. However, the European Union defines eggshells as low-risk material that can be recycled and reused safely in other applications. Their chemical composition renders them an attractive precursor of calcium phosphate materials (CaPs). Because of their remarkable biocompatibility and capacity for natural degradation, CaPs are frequently employed in biomedical engineering applications. In this research, the wet precipitation method was employed for fabricating CaP powder. Initially, the eggshells were processed into CaCO3 powder and then reacted with HCl to obtain CaCl2 (aq). This reacted with Na2HPO4 to obtain a precipitate that was filtered and dried. The precipitate in powder form underwent X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) analysis to evaluate its microstructure, and elemental and phase composition. The results indicated that the recovered powder was brushite.